1‐ und 2‐Brompropan – Bestimmung von 1‐ und 2‐Brompropan in Urin mittels dynamischer Headspace‐GC/MS [Biomonitoring Methods in German language, 2019]. Issue 1 (30th January 2019) - Roßbach, B.; Rißler, E.; Budnik, L.T.; Finger, S.; Göen, Th.; Hartwig, A.; ,
Abstract: The working group "Analyses in Biological Materials" of the Permanent Senate Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area verified the presented biomonitoring method. The analytical method described herein permits the sensitive determination of both unmetabolised 1‐bromopropane and 2‐bromopropane in urine. Prior to the determination using GC‐MS in the Single‐Ion‐Mode (SIM), the analytes are extracted and enriched using Headspace Solid Phase Dynamic Extraction (SPDE). To this end, the urine samples are incubated at 50 °C and the analytes are extracted from the gas phase using SPDE. The headspace extract is then injected into the gas chomatograph for separation and mass spectrometric analysis. Calibration standards are prepared in urine and processed in the same way as the samples to be analysed. Deuterated benzene is used as the internal standard (IS).